Challenges in the Management of Hepatitis B Among Children and Adolescents: A 10-Year Single-Center Experience - Anna Dobrzeniecka; Ewa Talarek; Małgorzata Aniszewska; Barbara Kowalik-Mikołajewska; Agnieszka Ołdakowska; Beata Krynicka-Czech; Magdalena Marczyńska; Maria Pokorska-Śpiewak (Microorganisms, 2026)
Following successful neonatal HBV vaccination and perinatal screening, pediatric hepatitis B has become uncommon in Central Europe. However, migration and complex clinical scenarios are reshaping its epidemiology. We aimed to characterize the clinical course, disease phases, and treatment eligibility of children with HBV infection. This retrospective single-center study included patients aged 0 to